(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1975)
The objective of the present paper was the justification of federal regulations that compulse the storage of sodium chloride treated infected meat for 21 days. Using infected peaces of meat collected from the slaugheter horses the effecace of sodium chloride rubbings was determined under laboratory conditions. The inactivation of C. cellulosae was correlated with time necessary to obtain this complete inactivation.